Hubungan Persepsi Terhadap Harapan Orang Tua dengan Stres Akademik pada Siswa Kelas Unggul Tahfidz di MTsN X Bukitinggi - Yulianti, Fitri; Yusra, Zulmi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to investigate the correlation between perception of parental expectations and academic stress in tahfidz class students in MTsN 1 Bukittinggi city. This study uses a correlational quantitative method. Data collection was carried out offline by distributing questionnaires. The technique in taking samples was carried out in total sampling, involving 95 students from the superior class of tahfidz grades 7, 8, and 9 as participants. The data produced was analyzed using a product moment correlation test. The results of this study showed a significant positive correlation between students' perception of parents' expectations and the level of academic stress among students of the superior class of tahfidz in MTsN 1 Bukittinggi City, with a correlation coefficient value of 0.705. This shows that the higher the perception related to parental expectations, the higher the academic stress of tahfidz class students in MTsN 1 Bukittinggi City.